Criação e Transporte de Ninfas de Ephemeroptera (Insecta) em Campo - Boldrini, Rafael; Cruz, Paulo Vilela (EntomoBrasilis, 2013)
Muitas espécies de Ephemeroptera são conhecidas somente em um estágio, normalmente adulto ou ninfa. Nesse estudo é proposto uma metodologia para transporte e criação de ninfas em campo Rearing and Transport of Mayfly Nymphs in the Field Abstract. Many species of Ephemeroptera are known in only one phase, adult or nymph. In this study, we propose a methodology for transport and rearing nymphs in the field.